Divergent and Diastereoselective Synthesis of α-Monosubstituted and trans-α,β-Disubstituted γ-Lactams from (S)-N,N-Dibenzyl-α-amino Aldehydes via Henry and Michael Reactions - P. Meirelis, Francine; Vieira, Bruna G. N.; Pereira, Vera L. P. (Synthesis, 2020)
γ-Monosubstituted and trans-α,β-disubstituted γ-lactams were diastereoselectively synthesized from common intermediates (S)-N,N-dibenzylated aldehydes derived from natural l-(α)-amino acids, employing a divergent approach. The key features of the routes include diastereoselective Henry and Michael reactions that produced chiral γ-nitroester derivatives, which were subsequently submitted to a tandem reduction-lactamization sequence providing the title compounds. The versatility of routes can allow the preparation of several other mono-, di-, or tri-substituted γ-lactams.
Keywords: divergent synthesis; Michael addition; Henry reaction; γ-lactams; domino reaction; diastereoselective synthesis; 1,3-dicarbonyl compounds